Complex interplay between depositional and petrophysical environments in Holocene tidal carbonates (Al Ruwais, Qatar). Issue 6 (10th April 2017) - Purkis, Sam; Rivers, John; Strohmenger, Christian J.; Warren, Christopher; Yousif, Ruqaiya; Ramirez, Luis; Riegl, Bernhard
Abstract: Carbonate rocks can be classified in terms of those properties relating to the pore system of lithified sediments, so‐called 'petrophysical rock types', or 'depositional rock types' which are categorized based on characteristics directly reflecting their original depositional environment. Whereas petrophysical rock types are typically used to identify and distribute rock bodies within a reservoir with similar flow characteristics, depositional rock types ignore pore types and capture sedimentary structures, lithology and fossils. Both classification systems are extensively used to describe reservoir rocks, but the degree of plurality between them remains poorly understood and is the motivation for this study. To examine the degree of congruency between the two classification schemes, a field assessment was conducted for a 175 km 2 area situated offshore Al Ruwais, northern Qatar, encompassing depositional environments spanning supratidal, intertidal, shallow subtidal and open marine conditions. A total of 350 surficial sediment samples were collected along 24 shore‐normal transects. Each sample was assigned a 'petrophysical rock type' class based on analysis of sedimentary texture (grain size and sorting). 'Depositional rock type' classes, by contrast, were defined with reference to faunal content and, in turn, classes of mineralogy were delimited by weighting this content against the mineralogy of each faunal category. Of course, the samples studied correspond to unconsolidated sediments and not to indurated rocks. However, considering only primary porosity and permeability preservation, it is reasonable to assume that the classified sediments would become petrophysical rock types and depositional rock types when consolidated, following their primary grain size, sorting and grain type distribution. Therefore, the term 'rock type' is retained here for ease of terminology but, for clarity, these are sediment samples. The discrete samples were interpolated into continuous surfaces describing the distribution of depositional rock types, petrophysical rock types and mineralogy, and spatial correspondence between those surfaces was statistically evaluated. In order to link these parameters with environment of deposition, their correlation with water depth (as audited from airborne light detection and ranging) and ecological habitat (mapped from DigitalGlobe satellite imagery) was also assessed. The data reveal that spatial distributions of sedimentary faunal, petrographic and mineralogical properties do not show exactly congruent patterns. Other meaningful trends do exist, however. For example, the occurrence of certain depositional rock types is indicative of particular petrophysical rock types, and vice versa. Further, connections between petrophysical rock types and mineralogy are emphasized and offer insight as to how the evolution of matrix porosity might be predicted via diagenetic models tuned to specific sediment textures. Useful relationships are also identified between the occurrence of petrophysical rock types and depositional rock types, and both ecological habitat and water depth. The potential of such dualities is two‐fold. Firstly, they can be applied to more realistically distribute petrophysical rock types and depositional rock types by environment of deposition in reservoir models and, secondly, the use of modern carbonate systems as subsurface analogues might be enhanced.